Analysis of the shedding of three β‐herpesviruses in urine and saliva of children with renal disease. Issue 3 (16th October 2013) - Yamamoto, Yasuto; Morooka, Masashi; Hashimoto, Shuji; Ihra, Masaru; Yoshikawa, Tetsushi
Abstract Cytomegalovirus (CMV), human herpesvirus 6 (HHV‐6) and 7 (HHV‐7) are important pathogens in immunocompromised patients. To elucidate the kinetics of the three β‐herpesviruses in saliva and urine samples were collected serially from children with renal diseases. Twenty children with renal diseases were enrolled in this study. A total of 240 saliva and urine samples were collected monthly from the patients over a 1‐year period. Viral DNAs loads were measured by real‐time PCR. In 10 CMV seropositive patients CMV DNA was detected rarely in saliva and CMV DNA load was lower than the other two β‐herpesviruses DNA loads. All patients were seropositive for HHV‐6B and the virus was detected frequently in saliva. Two of 20 patients were HHV‐7 seronegative. High copies of viral DNA were detected continuously in saliva of the HHV‐7 seropositive patients. Although neither CMV nor HHV‐6B DNA load was different among the three renal diseases, HHV‐7 DNA load was different among the diseases (P = 0.039). HHV‐6B DNA loads were significantly higher in patients with immunosuppressive treatment compared to those without treatment (P = 0.013). Although CMV DNA was detected in urine samples collected from 5 of 10 CMV seropositive patients, HHV‐6B and HHV‐7 DNA were detected at relatively low frequencies in urine. No remarkable temporal associations between viral DNA excretion and proteinuria or immunosuppressive treatment were demonstrated. The pattern of viral DNA excretion in saliva and urine were different among the three viruses. No temporal correlation was observed between viral infection and renal diseases. J. Med. Virol. 86:505–511, 2014. © 2013 Wiley Periodicals, Inc.